2022
DOI: 10.1021/acs.nanolett.2c02881
|View full text |Cite
|
Sign up to set email alerts
|

Stable Negative Optical Torque in Optically Bound Nanoparticle Dimers

Abstract: Negative optical torque is a counterintuitive optomechanical phenomenon that can emerge in light-assembled nanoparticle (NP) clusters (i.e., optical matter) under circular polarization. However, in experiments, stable negative torque was limited to optical matter with 3 or more NPs. Here, we show that by increasing the particle size, the sign of optical torque can be reversed in optical matter dimers, where stable negative torque arises in dimers of 300 nm diameter Au or 490 nm diameter polystyrene NPs. Our co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Optical binding of the NPs was studied by using a holographic optical tweezer setup with an inverted microscope. [ 18 ] A Gaussian laser beam (λ = 800 nm in air) generated by a Ti:sapphire laser was shaped into two types of optical lines by a spatial light modulator using convex cylindrical lens holograms, [ 7b ] where the polarization of light is either parallel or perpendicular to the line. The laser power was measured to be 90.8 mW after the objective for the 150 nm NPs and 118.3 mW for the 100 nm NPs.…”
Section: Methodsmentioning
confidence: 99%
“…Optical binding of the NPs was studied by using a holographic optical tweezer setup with an inverted microscope. [ 18 ] A Gaussian laser beam (λ = 800 nm in air) generated by a Ti:sapphire laser was shaped into two types of optical lines by a spatial light modulator using convex cylindrical lens holograms, [ 7b ] where the polarization of light is either parallel or perpendicular to the line. The laser power was measured to be 90.8 mW after the objective for the 150 nm NPs and 118.3 mW for the 100 nm NPs.…”
Section: Methodsmentioning
confidence: 99%
“…The red area shows the regime for positive optical torque (push), and the blue that for negative optical torque (pull). Reprinted with permission from ref . Copyright 2022, American Chemical Society.…”
Section: A New Strategy For Nanomotors: Applying Negative Torque To S...mentioning
confidence: 99%
“…Termed negative optical torque, Prof. Yan and coauthors demonstrated that this phenomenon can be generalized to create a very simple construct: dimers of nanoparticles (in this case, both polystyrene and gold nanoparticles). 2 The torque can be switched optically by tuning the sizes of the particles, and other nuanced factors, which changes the spin-to-orbital angular momentum conversion. The simplicity of the two-particle construct enables new designs for light-powered nanomotors (see Figure 1).…”
mentioning
confidence: 99%
“…Although a CPL has only SAM but without orbital angular momentum (OAM) intrinsically, CPL may induce the optical binding between two individual GNPs to form a dimer with a stable distance, and drives them to rotate around their center of mass (COM) accompanied with individual spinning [16]. Of interesting, the rotation's direction of dimer not only depends on the handedness of CPL but also the size of GNPs [17][18][19]. For a smaller GNP/SNP dimer, the rotational direction is always consistent with the handedness of CPL.…”
Section: Introductionmentioning
confidence: 99%
“…For a smaller GNP/SNP dimer, the rotational direction is always consistent with the handedness of CPL. In contrast, for a larger GNP/SNP dimer a reverse rigid-body rotation around the COM may be induced due to the negative optical torque caused by higher-order modes [17][18][19]. Moreover, using CPL to manipulate multiple SNPs, GNPs or GNRs have also been studied [4,7,15,18,20].…”
Section: Introductionmentioning
confidence: 99%